Using the Timely Computing Base for Dependable QoS Adaptation - Casimiro, António (2001)
In open and heterogeneous environments, where an unpredictable number of applications compete for a limited amount of resources, executions can be affected by also unpredictable delays, which may not even be bounded. Since many of these applications have timeliness requirements, they can only be implemented if they are able to adapt to the existing conditions. Adaptation can be done by several ways, taking into account many different factors, but an obvious factor of success is knowing what they have to adapt to. In this paper we present a novel approach, called Dependable QoS adaptation, which can only be achieved if the environment is accurately and reliably observed. Dependable QoS adaptation is based on the Timely Computing Base (TCB) model. The TCB model is a partial synchrony model that adequately characterizes environments of uncertain synchrony and allows, at the same time, the specification and verification of timeliness requirements. We introduce the coverage stability property and show that adaptive applications can use the TCB to dependably adapt and enjoy this property. We describe the characteristics and the interface of a QoS coverage service and discuss its implementation details